Branding in B2B: the value of consumer goods brands in industrial markets. Issue 3 (3rd April 2017) - Viardot, Eric
Abstract : Purpose: This paper aims to explore whether consumer goods brands (CGBs) have more brand equity than exclusively professional brands (EPBs) do in the context of the industrial detergents market. Design/methodology/approach: The author conducted direct customer interviews at the outlets of two large wholesale distribution retail chains. The sample included 211 respondents. Findings: The study shows that CGBs do have brand equity in business-to-business (B2B) market. First, they enjoy a greater top-of-mind awareness than do EPBs. Second, they have a distinctive brand image, as they are perceived as being more efficient and more expensive than are EPBs. Research limitations/implications: There are three main limitations. First, the results may reflect industry-specific factors that are not representative of all professional markets. Second, the products studied are relatively low in price compared to other categories of professional products. Third, the sample market is a mature market characterized by a modest growth rate and limited development in related markets. However, these limitations do not discredit the results of the study. Conversely, they invite further research on the subject of CGBs extending into professional markets. Future research could examine other product categories as well as the use of an experimental approach to validate and generalize the primary results. Practical implications: This research has implications for business-to-consumer marketing professionals looking to leverage the equity of their CGBs in the B2B space. In addition, this work can help B2B marketing professionals better defend their market share in the face of well-known CGB entering their market. Originality/value: This study represents an exploratory analysis, as the author has not any found prior work on this topic. In addition to these original results, the paper contributes to a better understanding of the concept of brand equity in B2B for academics and provides new insights for industrial marketers regarding branding in B2B.